Effect of different phosphorus levels and varieties on the productivity of cowpea (Vigna unguiculata L.) at Khairahani, Chitwan, Nepal - Aryal, Aashish Bandhu; Dhakal, Sagar; Poudel, Aakriti; Aryal, Bibek; Adhikari, Bishnu Bilas (Journal of Agriculture and Natural Resources, 2025)
A field experiment was undertaken during the summer season of 2023 at Khairahani, Chitwan, with the objective of evaluating the effect of different phosphorus levels on the growth, yield attributes, and grain yield of two cowpea (Vigna unguiculata L.) genotypes and determine the optimum phosphorus dose for higher productivity under rainfed lowland conditions. Two cowpea genotypes, namely Surya and Gajale, and four phosphorus levels (0, 20, 40, and 60 kg P₂O₅/ha) were evaluated in a two-factor factorial Randomized Complete Block Design (RCBD) with three replications. The height of the plants, the index of leaf area, the length of the pods, and the number of pods on one plant were, however, not affected at all by the cowpea varieties or the phosphorus levels. The Gajale variety along with the highest phosphorus level (60 kg P₂O₅/ha) recorded the maximum number of grains per pod (12). On the contrary, grain yield was heavily depending on the variety and the phosphorus application, with the Gajale variety produced the highest yield (1.19 t/ha) and at 60 kg P₂O₅/ha (1.24 t/ha), followed by 40 kg P₂O₅/ha (1.13 t/ha). The interaction between cowpea varieties and phosphorus levels was observed to be statistically significant and thus, the Gajale variety with 60 kg P₂O₅ /ha obtained the maximum grain yield (1.35 t/ha). Hence, it can be stated that the cultivation of Gajale variety with the application of 60 kg P₂O₅/ha under rainfed lowland conditions in eastern Chitwan is the producer of cowpea productivity in the highest way possible.